ANALISIS PENILAIAN KONSUMEN TERHADAP LAYANAN MEDICAL CHECK UP STUDI EMPIRIS DI RSUD KOTA BOGOR - Sonia Redmana; Indupurnahayu, Indupurnahayu; Asri Masitha Arsyati (Bajang Institute, 2025)
The purpose of this study was to analyze consumer ratings of Medical Check Up services, one of the promotive and preventive efforts that can find early diagnoses so the potential health problems can be dtercterd early in RSUD Kota Bogor. Quantitiative reseach method, primary data with a population of 2.615 dan a sample of 96 using quantitative analysis with a cross-sectional study design approach, collecting data by distributing questionnaires, dimensions of tangible, reability, responsiveness, assurance and empathy. Descriptive data analysis, Fishbein analysis, Corelation Analysis Pearson Product Moments. Ther result of the study, 52.08% of service users were women, the most aged 26-35 years weew 36.46%, the most professions werw 35.42% private employees. The results of data analysis show that the relationship between consumer trust and the five dimensions of tangible, reability, responsiveness, assurance and empathy, sostumers stated that the Medical Check Up service at RSUD Kota Bogor was included in the positive category. There is very strong relationship between consumer ratings and consumer trust. The result of this study can be used as a reference to improve the quality of service at RSUD Kota Bogor.